2014
DOI: 10.1371/journal.pone.0098965
|View full text |Cite
|
Sign up to set email alerts
|

lnCeDB: Database of Human Long Noncoding RNA Acting as Competing Endogenous RNA

Abstract: Long noncoding RNA (lncRNA) influences post-transcriptional regulation by interfering with the microRNA (miRNA) pathways, acting as competing endogenous RNA (ceRNA). These lncRNAs have miRNA responsive elements (MRE) in them, and control endogenous miRNAs available for binding with their target mRNAs, thus reducing the repression of these mRNAs. ln Ce DB provides a database of human lncRNAs (from GENCODE 19 version) that can potentially act as ceRNAs. The putative mRNA targets of human miRNAs and the targets m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
109
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(110 citation statements)
references
References 40 publications
0
109
0
Order By: Relevance
“…It has been reported that lncRNAs affect post-transcriptional regulation by interfering with miRNA pathways, acting as ceRNAs [45] . Our study also revealed that GAS5 can be used as a "molecular sponge" to block and bind miR-23a, thereby positively modulating the miR23a targeted autophagy-related gene ATG3.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lncRNAs affect post-transcriptional regulation by interfering with miRNA pathways, acting as ceRNAs [45] . Our study also revealed that GAS5 can be used as a "molecular sponge" to block and bind miR-23a, thereby positively modulating the miR23a targeted autophagy-related gene ATG3.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, lncRNAs have been shown to bind both miRNA themselves and miRNA binding sites on their target mRNAs, thus modulating miRNA activity (Fig.1K). Competing endogenous lncRNAs (termed ceRNAs [20]), which act as miRNA sponges, include, for example lncRNA CHRF, which has been shown to bind miR-489, reducing its availability for downregulating Myd88 mRNA [70]. In other examples, linc ROR blocks miR-145 [71]; lncRNA PTENP1 modulates endogenous PTEN transcript levels by acting as a molecular sponge for PTEN-targeting miRNAs [72]; linc-MD1 is a muscle-specific lncRNA which activates the expression of MAML1 and MEF2C by sponging up miR-133 [73].…”
Section: Lncrna Biologymentioning
confidence: 99%
“…The 132 identified bifunctional RNAs were mapped to the ceRNA candidates documented in the lnCeDB database (Das et al, 2014) and 26 bifunctional RNAs were matched. In summary, those 26 bifunctional RNAs can act as ceRNAs to compete with related RNAs for 963 targeting miRNAs, which may result in changes in expression levels of corresponding RNAs.…”
Section: Bifunctional Rnas May Function As Competing Endogenous Rnasmentioning
confidence: 99%
“…We also examined the expression correlatio between bifunctional RNAs and their targeting miRNAs using miRGator V3.0 (Cho et al, 2013) in different cancer and normal tissues. To interrogate whether bifunctional RNAs could act as ceRNAs to regulate the expression of relevant genes, we checked their existence in the ceRNA candidates cataloged in lnCeDB database (Das et al, 2014). The cancer related genes of diverse human cancers from the databases of NCG4.0 , TSGene (Zhao et al, 2013) and two previous studies about human pan-cancer (Kandoth et al, 2013;Vogelstein et al, 2013) were collected as well.…”
Section: Characterization and Annotation Of Bifunctional Rnasmentioning
confidence: 99%